Technical Writing for Technicians - Fleming, Will (Open textbook library., 2020)
Technical Writing for CTE is an open source e-textbook designed specifically for use in LBCC’s WD4 (Technical Writing for Welders) and all versions of IN4 (Technical Writing for CTE).